A Case Study on English Speaking Anxiety in Language Learning Classroom of Non-Major Students of STIT Palapa Nusantara Lombok-NTB: Kecemasan Berbicara Bahasa Inggris di Kelas Pembelajaran Bahasa Pada Mahasiswa Non-Jurusan (Studi Kasus STIT Palapa Nusantara Lombok) - Ozi Satria (Al-Gafari : Manajemen dan Pendidikan, 2025)
The aims of this research was to analyze the non-major students’ speaking anxiety in language learning classroom. The subject of this research was the 2nd grade students of the study program of Islamic Educational Management (MPI) of STIT Palapa Nusantara Lombok. This research investigated various categories of anxiety and their causal factors. The research utilized a case study feature. The data were collected through classroom interaction observations and interviews. The data were then analyzed and interpreted to answer the research questions. This research achieved two results related to the research questions. First, the researcher obtained three proven categories of anxiety such as Anxious Nature, Contextual Anxiety, and State Anxiety. The category of students’ speaking anxiety was based on Elis theory. Furthermore, the researcher gained three causal factors that brought up the students’ speaking anxiety such as Speech Anxiety, Exam Anxiety, and Dread of Negative Evaluation. The causal factors of students’ speaking anxiety was based on Horwitz theory. Additionally, pupils have speaking anxiety due to a lack of vocabulary and grammatical skills. Thus, on behalf of forcing the students to be more confident, eloquent, and disappear their anxiety to speak, lecturers should uplifting them by having brilliant approach and creativity in teaching and learning process.